Pengaruh Kelelahan Otot Ekstremitas Bawah Terhadap Gerakan Mendarat/Landing Satu Kaki Pada Pemain Futsal Putra - Zacky Zakaria Muslim; Agus Rusdiana; Iwa Ikhwan Hidayat (Universitas Galuh, 2025)
ABSTRACTLower extremity muscle fatigue is a significant factor affecting the landing mechanics of one-footmovements in futsal players. This study aimed to analyze the impact of lower extremity muscle fatigue onthe kinematic parameters of landing movements. The research involved 14 male futsal players using aquantitative descriptive method with a pre-test and post-test design. The research instruments included theBosco test (squat jump, countermovement jump, and lunges), a force plate, and blood lactate measurements.Results indicated a significant increase in blood lactate levels post-fatigue (p < 0.05). Additionally,significant differences were observed in hip, knee, and ankle joint angles before and after fatigue. Fatiguereduced neuromuscular control, increased injury risk, and impaired landing stability. In conclusion, lowerextremity muscle fatigue negatively impacts landing biomechanics, highlighting the need for strengthtraining and fatigue management to prevent injuries and enhance performance.